A comparative study of endoscopic versus conventional septoplasty - Dhaka, Ramniwas; Arya, Pooja; Chand, Deep; Samor, Vivek; Bishnoi, Ramchander; Khadav, Sukhdev (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Deviated nasal septum is one of the common causes of nasal obstruction. Correction of deviated nasal septum has been performed by a variety of techniques of which Septoplasty is the most popular one. With the advent of endoscopes and their successful use in endoscopic sinus surgery endoscopes have been tried in septoplasty for better visualization of posterior part of septum and do the surgery more precisely and with less complication as compare to conventional method. The objectives of the study were to compare the outcomes of conventional and endoscopic septoplasty, to evaluate the advantages, disadvantages and complications of both endoscopic and conventional septoplasty. Methods: It was a prospective observational study conducted on 50 patients with deviated nasal septum, who presented to ENT department of SPMC, Bikaner, patients were randomly divided equally in two groups for conventional and endoscopic septoplasty respectively. Data collected on a prestructured proforma and results analysed. Results: The study included 50 cases. Postoperatively significant relief from the symptoms of nasal obstruction (82%) in group A and (96%) group B, was seen. In objective assessment at the end of 3 months of surgery, patient had persistent posterior deviation 24% in group A and 3% in group B, spur 12% in group A and 0% in group B. Conclusions: Endoscopic septoplasty has an obvious edge over the conventional approach due to better illumination which enables to identify the pathology accurately, excise the deviated part of septum precisely and realignment of the cartilage for best results.